Ibu(isme) dan Film Orde Baru: Representasi Ibu dalam film Jangan Menangis Mama - Kurnia, Novi; Hidayatullah , Mochammad Taufik (Jurnal Komunikasi, 2024)
The representation of women in films is always an interesting topic in Indonesian film studies. This article aims to reveal the representation of women, especially in their identity as mothers in the film Jangan Menangis Mama (Don’t Cry Mommy) was produced in 1977. This film was directed by Sofia WD, a film star, screenwriter, and film producer who works both in the Old Order and the New Order of the Indonesian Film Industry. Based on Roland Barthes' semiotic analysis, this article uncovers two levels of meaning systems, namely denotation and connotation related to the mother's character in the film. The process of interpreting these signs cannot be separated from the concept of ‘ibuism’ (motherhood) as a gender-political ideology of the New Order and the context of the male-dominated film industry. Research findings show that the dominant representation of mothers is associated with the weak position of a woman with various roles: as a wife, a mother, a single mother, a citizen, and a daughter. However, this research found a 'limited' agency from Sofia WD as a woman director of the film Jangan Menangis Mama to offer gender representation that is not completely stereotypical as well as not just 'black and white' as in previous studies.